2022
DOI: 10.3847/2041-8213/ac64a5
|View full text |Cite
|
Sign up to set email alerts
|

Apples and Oranges: Comparing Black Holes in X-Ray Binaries and Gravitational-wave Sources

Abstract: The component black holes (BHs) observed in gravitational-wave (GW) binary black hole (BBH) events tend to be more massive and slower spinning than those observed in black hole X-ray binaries (BH-XRBs). Without modeling their evolutionary histories, we investigate whether these apparent tensions in the BH populations can be explained by GW observational selection effects alone. We find that this is indeed the case for the discrepancy between BH masses in BBHs and the observed high-mass X-ray binaries (HMXBs), … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 89 publications
3
22
0
Order By: Relevance
“…These differences, which can lead to high-spin BHs, are important to consider when interpreting observations. Our conclusions are in agreement with Fishbach & Kalogera (2022), who found that a subpopoulation comprising of at most 30% of BBHs may have features resembling rapidly spinning HMXB-like systems, where one BH component is high-spin. This is also in agreement with Neijssel et al (2021), who, following a case study of Cygnus X-1 and finding a 5% probability that it will result in a merging BBH within a Hubble time, infer that a small fraction of HMXBs like Cygnus X-1 may form BBHs.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…These differences, which can lead to high-spin BHs, are important to consider when interpreting observations. Our conclusions are in agreement with Fishbach & Kalogera (2022), who found that a subpopoulation comprising of at most 30% of BBHs may have features resembling rapidly spinning HMXB-like systems, where one BH component is high-spin. This is also in agreement with Neijssel et al (2021), who, following a case study of Cygnus X-1 and finding a 5% probability that it will result in a merging BBH within a Hubble time, infer that a small fraction of HMXBs like Cygnus X-1 may form BBHs.…”
Section: Discussionsupporting
confidence: 93%
“…However, considering BH spins, the merging population of BBHs may include only a small subpopulation of systems that are HMXB-like (systems containing a rapidly spinning component with χ 0.8, and preferentially aligned with the orbital angular momentum axis, as expected from isolated binary evolution). Conservatively, Fishbach & Kalogera (2022) find that a HMXB-like population can make up at most 30% of merging BBH systems. It is therefore important to understand how the specific evolutionary pathways of merging BBHs and HMXBs shape their observed spins distributions (Liotine et al 2022, in prep.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…On the one hand, our results stress once more that the inconsistency of the spin measurements obtained via any two (or more) of the available 'electromagnetic' methods (timing, continuum fitting, reflection spectroscopy, and reverberation) is symptomatic of an inexact, or at least inaccurate, modelling of the data. On the other hand, if the RPM is correct, our results alleviate the tension between the gravitational waves (see Wysocki & Ligo-VIRGO-Kagra Collaboration 2022;Golomb & Ligo-VIRGO-Kagra Scientific Collaboration 2022) and the electromagnetic spin measurements (Fishbach & Kalogera 2022), and supports the hypothesis that LIGO/Virgo BHs and X-ray binary BHs do not necessarily form two distinct populations (Belczynski et al 2021).…”
Section: Discussionsupporting
confidence: 80%